2015
DOI: 10.1186/s40902-015-0039-8
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of changes in pharyngeal airway space and position of hyoid bone after mandibular setback surgery by cephalometric analysis

Abstract: BackgroundThe posterior movement of mandible was known as the main cause of the changes in the pharyngeal airway space (PAS) and the postoperative obstructive sleep apnea (OSA). The purpose of this study was to know the changes of PAS and position of hyoid bone.MethodsLateral cephalographies of 13 patients who had undergone sagittal split ramus osteotomy (SSRO) setback surgery were taken preoperatively (T1), postoperatively within 2 months (T2), and follow-up after 6 months or more (T3). On the basis of F-H pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The position of the hyoid bone is commonly determined by lateral cephalometric analysis, for purposes including maxillofacial surgery, diagnosis of sleep apnea, and analysis of skeletal patterns and occlusions [9][10][11] . Although cephalometric radiography is commonly used in orthodontic treatment, the modality remains rare ; routine dental care would benefit from precise identification of hyoid bone location using a more common modality, such as panoramic radiography.…”
Section: Introductionmentioning
confidence: 99%
“…The position of the hyoid bone is commonly determined by lateral cephalometric analysis, for purposes including maxillofacial surgery, diagnosis of sleep apnea, and analysis of skeletal patterns and occlusions [9][10][11] . Although cephalometric radiography is commonly used in orthodontic treatment, the modality remains rare ; routine dental care would benefit from precise identification of hyoid bone location using a more common modality, such as panoramic radiography.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6]17 The literature states that the hyoid bone was significantly displaced downward and backward immediately 1 month after mandibular setback surgery and gradually returned to its original position within 6 months of surgery. 17,22,48 This displacement can affect the PAS and may justify the score changes (T1, T2) in our results. According to the results established by Kitagawara et al, SpO2 decreased during the immediate postoperative period after mandibular setback surgery, but improved after 1 month, and also postoperative edema almost completely resolved within 1 month after surgery, hence the second time interval was set at 1 month postoperatively.…”
Section: Discussionmentioning
confidence: 64%
“…After surgery, the entire tongue moves posteriorly (or anteriorly), and the distance between the tongue and the anterior teeth of the plate changes, giving an impression that MTP decreases temporarily. Previous studies on oral function in patients with jaw deformities have reported that the MTP changes within a few months after surgery to adapt to the new postoperative environment [ 16 , 26 , 27 ]. Another report indicated that MTP after SSRO tends to increase over 1 year after surgery.…”
Section: Discussionmentioning
confidence: 99%